"That is when I changed and my whole life changed": Turning points in health perceptions among LGBTQ adults of color. Issue 2 (4th March 2022) - Hudson, Kimberly D.; Mehrotra, Gita R.
ABSTRACT: This study explored turning points in health perceptions among lesbian, gay, bisexual, transgender, and queer (LGBTQ) adults of color living in a major US city. Turning points in health perceptions were elicited from 38 participants through in-depth interviews and were examined using interpretive phenomenological analysis. Findings revealed three key themes: (a) diagnosis and disease; (b) death or illness of family and friends; and (c) changes in environmental context and body. The positive impacts of turning points are discussed, including the development of active coping skills, engagement in health-promoting behaviors, and increased community connectedness. Implications for future research are also suggested.